Are natural floods accelerators for streambank vegetation development in floodplain restoration?. Issue 1 (24th December 2021) - Stammel, Barbara; Stäps, Julia; Schwab, André; Kiehl, Kathrin
Abstract: Riverbanks are very dynamic habitats for riparian vegetation strongly influenced by fluvial and geomorphic processes. This habitat type was severely reduced in the past by river straightening and bank stabilisation. Restoration and establishment of new floodplain streams promote this habitat, but a directed succession to later stages was observed many times. Our study aimed to analyse whether the often observed directed succession of the streambank vegetation after restoration implementation could be reversed by a natural flood along a newly created floodplain stream. We investigated the effects of a natural flood in 2013 and different prerestoration conditions on species development in the riparian zone. Vegetation was studied along 12 transects in four different sections from 2011 to 2014. Species composition differed strongly between the sections. Species richness was lowest in a newly dug steep section with high morphological dynamics and highest on wider flat streambanks. Changes during the years reflecting different hydrological events varied between sections. The high natural flood in 2013 reduced the cover of the herb layer and increased bare ground, which led in most sections to a loss of nontarget species. Total target species richness did not change due to the natural flood, while target species showed a high turnover rate. In the following year, however, the flood‐induced development of species composition, in general, was reversed. Natural floods changed abiotic and biotic conditions along the streambank, but they did not accelerate ecological restoration towards predefined target ecosystems. However, they were necessary to preserve the needed dynamic vegetation changes and species turnover to hinder the succession to later stages dominated by a few species. Our study shows that riparian vegetation near the streambank can be monitored most effectively in cross‐profile transects, both in the long‐term and event‐related.